Teaching children to read - Central Ohio Educational Research Council. (The Ohio State University, 1973-74, 1973)
Provides suggestions and resources for the effective teaching of reading.
Bibliography: p. 116-119
Cover title: Reading guide.
Provides suggestions and resources for the effective teaching of reading.
Keywords: Reading / Study and Teaching.